2015
DOI: 10.18671/scifor.v43n108.3
|View full text |Cite
|
Sign up to set email alerts
|

Enraizamento de miniestacas de eucalipto com diferentes doses de polímero hidroretentor incorporado ao substrato

Abstract: Enraizamento de miniestacas de eucalipto com diferentes doses de polímero hidroretentor incorporado ao substrato Minicutting rooting of eucalyptus with different doses of the hydrophylic polymer incorporated into the substrate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 10 publications
1
12
0
2
Order By: Relevance
“…The results obtained in the present work corroborate in part with those obtained by Azevedo et al (2015), which evaluated the effect of hydrogel rates on rooting of mini-cutting of VM01 and AEC0144 clones (E. urophylla), (vermiculite, charcoal rice husk and coconut fiber (1: 1: 1)). These authors verified that, for the clone VM01, the traits SM, RM, NR, RSL, MRL and RSDM were influenced by different hydrogel rates incorporated into the substrate; for clone AEC0144, this effect was verified only for the SM, RM and MRL traits.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The results obtained in the present work corroborate in part with those obtained by Azevedo et al (2015), which evaluated the effect of hydrogel rates on rooting of mini-cutting of VM01 and AEC0144 clones (E. urophylla), (vermiculite, charcoal rice husk and coconut fiber (1: 1: 1)). These authors verified that, for the clone VM01, the traits SM, RM, NR, RSL, MRL and RSDM were influenced by different hydrogel rates incorporated into the substrate; for clone AEC0144, this effect was verified only for the SM, RM and MRL traits.…”
Section: Resultssupporting
confidence: 89%
“…For each substrate, seedlings were produced with and without hydrogel incorporation. The hydrogel used was the Forth Gel  , at a rate of 2 g L -1 of the substrate (AZEVEDO et al, 2015), incorporated in its dehydrated form. The basis fertilization used was the same used in the nursery seedlings production system (29.16 g of Basacote  and 12.15 g of Yorin master  , for every 14 L of the substrate).…”
Section: Seedling Production Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The same doses of this hydrogel were also tested by Azevedo et al (2015) on the rooting capacity of minicuttings of different eucalypt clones. The authors concluded that the efficiency of this hydrogel makes it a promising alternative for improving rooting of eucalyptus minicuttings, especially for those clones that naturally have low rooting rates.…”
Section: Silviculturamentioning
confidence: 99%
“…As mesmas doses desse hidrogel também foram testadas por Azevedo et al (2015) no enraizamento de miniestacas de diferentes clones de eucalipto. Os autores destacaram que a eficiência desse hidrogel o faz ser uma alternativa promissora à melhoria do enraizamento de miniestacas de eucalipto, sendo mais indicado a clones que naturalmente apresentam baixas taxas de enraizamento.…”
Section: Silviculturaunclassified